Pengurusan promosi acara Safari Rakit Baleh-Kapit di Pekan Kapit, Sarawak - Mohd Khairulnizam, Jamain (Universiti Malaysia Sarawak (UNIMAS), 2018)
The purpose of this research is to study and analyze topic related to the Event Promotion Management of Baleh-Kapit Safari at Kapit Town, Sarawak. The main challenge faced by event promotion management in attracting visitors or outsiders to the event. The three objectives of the study ate to identify the factors that cause the lock of tourist arrival to the event, study the promotional methods taken by the event management and suffest systematic promotional management of events. The methods used in this study are qualitative and quantitative method.